Otimismo da vontade, pessimismo da razão: English marxism, Anderson translation & integral journalism of New Left Review (or an international world-marxism in the street-fighting years of western europe) - Della Santa, Roberto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The following thesis deals with a certain kind of English Marxism, political-editorial activity of Perry Anderson and the integral journalism of the journal of ideas NEW LEFT REVIEW. Its conductive hypothesis is that the milieu of the so-called second generation of this New Left produced a genre of an internationalist «World-Marxism» in the street-fighting years (T. Ali) of Western Europe. The historical making of this intellectual project inserted in its cultural formation is a social process that gave birth to a coeval and coextensive doubledcharacter mediation activity: i) translation-form, i.e., insularization / particularization / nationalization of a continental socialist culture (France/Germany/Italy/Russia) in the Islands (UK) and, hence, ii) the journalism-form, or, its continentalization / universalization / internationalization of a sui generis kind of Marxism, consubstantieted in a nexus of identitydiversity on local and global. The contrasts and conclusions and predictions and performances necessarily deals with the genesis, development and metamorphosis of historians of social processes and critics of ideas such as Edward Palmer Thompson, Raymond Henry Williams and Eric John Hobsbawm vis-à-vis the intellectual group of Perry Anderson, Robin Blackburn & Tom Nairn. A history against the grain (W. Benjamin) imposes us the challenge of unrevealing the adjudicated consciousness that made the mediocre and inert socialist culture of Great-Britain the Liviest Republic of Letters of Contemporary Marxism in the last quarter of the Twentieth Century. The aphorism of «Pessimism/Optimism» reflected/refracted the history of NLR: beyond political common sense and before theoretical high abstraction is in order to repair the prism of NLR itself at the light of historical time. A critical revaluation of the ... - (Complete abstract click electronic access below)

A tese a seguir versa sobre determinado tipo de marxismo inglês, a atividade político-editorial de Perry Anderson e o jornalismo integral da revista de ideias NEW LEFT REVIEW. A hipótese diretiva é de que a milieu da assim-chamada segunda geração desta New Left elaborou um gênero de «Marxismo-Mundo»internacionalista nos anos das barricadas (Tariq Ali) da Europa Ocidental. O fazimento histórico deste projeto intelectual inserido em sua formação cultural é um processo social que alentou a uma coetânea e coextensiva atividade de mediação com um duplo caráter: i) a forma-tradução, ou, a insularização / particularização / nacionalização da cultura socialista continental (França/Alemanha/Itália/Rússia) nas Ilhas (Inglaterra) e, daí, ii) a forma-jornalismo, i.e., a sua continentalização / universalização / internacionalização de um tipo sui generis de marxismo, consubstanciado a partir dum nexo identidade-diversidade entre local e global. Os contrastes e as conclusões bem como as predições e os desempenhos lidam necessariamente com a gênese, devir e metamorfoses de historiadores de processos sociais e críticos de ideias tais como Edward Palmer Thompson, Raymond Henry Williams e Eric John Hobsbawm vis-à-vis o grupo intelectual de Perry Anderson / Robin Blackburn / Tom Nairn. Uma história a contrapêlo (Walter Benjamin) impõe o repto de desvelar a consciência autoadjudicada que fez da cultura socialista medíocre e inerte, da Grã-Bretanha, a mais viva República das Letras do marxismo contemporâneo do último quartel do Séc. XX. O aforisma «Pessimismo/Otimismo» refletiu/refratou a história da NLR: além do senso comum político e aquém da alta abstração teórica cabe restituir o prisma da NLR em si à luz do tempo histórico. Uma revalorização da trilogia... - (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Anderson, Perry; Socialismo - Inglaterra; Imprensa e politica; Socialism